Pengaruh Tata Letak Mesin Dan Pemeliharaan Mesin Terhadap Proses Produksi Pada Perusahaan Manufaktur Di Kawasan Jababeka I - Kasidjo; Lidya Amalia Putri (Jurnal Ekonomi dan Bisnis, 2022)
This research supported by a vision that production influenced by several factors therefore, may need to analyse factors influencing the production process. The production process influenced by a number of factors including the layout of machines and maintenance on an engine company. The study aimed to identify the layout of the production process, machine know the influence of the production process, machine maintenance and to know the layout of the machinery and engine production in manufacturing companies in the Industry Jababeka I Cikarang. Variables subjects in this study is the independent variable layout machine ( X1 ) and maintenance machine ( X2 ) while the dependent variable production (Y). The data it is processed using the assumption classic, analyse linear regression, multiple the hypothesis is partial and simultaneous through the SPSS 25 Version. The layout of the engine and engine maintenance is directly related to the production process. The result of multiple linear relationship is known to have had a positive impact on the process production. The result of the coefficients determined 51,8% of the production process described variable free and 48,2%  by other factors outside research. Test t ( partial ) variable layout a significant impact on production, variable production of significant impact on production process. Test f ( simultaneous ) variable layout machine and maintenance of a significant influence on the process production.